Microbial Communities in Peruvian Acid Mine Drainages: Low-Abundance Sulfate-Reducing Bacteria With High Metabolic Activity. - Valdez-Nuñez, L.F. (2022)
We investigated the microbial community composition in three different mine tunnels from Hualgayoc (Cajamarca, Peru) and the metabolic activity of acidophilic sulfate-reducing bacteria (aSRB) enriched from acidic sediments of the mining tunnels. Microbial community composition in environmental samples was analyzed by 16S rRNA amplicon sequencing. Metallibacterium and Acidiphilium were found as the most abundant bacteria in PM1 and PM2 sites, respectively, while Cyanobacteria was abundant in PM3 site. Isosphaera and Pseudomonas thrived in the acidic water of PM2 site as well. Sulfate reduction at low pH was then evaluated in microcosm experiments showing activity even at pH 3.4. Hydrogen was the most favorable electron donor in terms of sulfate reducing rates (0.5 mM day−1 at pH 5.1) and sulfide production (4.9 mM at the end of the experiment). Sequences affiliated to Desulfosporosinus and Desulfovibrio were abundant in the hydrogen microcosms (60.3 and 17.8%, respectively). These sequences were not detected in sediments, but their occurrence in the microcosms suggests their low abundance in the studied AMD systems. Our results expand the phyla detected in AMD environments and contribute to the understanding of aSRB for the possibility of applying these microorganisms in bioremediation.